Variasi Debit Air Dengan Daya Dihasilkan Turbin Air Vertikal Skala Kecil - Nurazizah, Junita; Anwar, Moh. Syaiful (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Hydroelectric power plants are the newest energy source that hasBgreat potential toBmeet electrical energy needs. On a small scale, hydroelectric power plants are an attractive option to meet energy needs in remote areas, and areas that are difficult to reach with traditional electricity infrastructure. The main component of a hydroelectric power plant is a water turbineBwhich has the task of converting the kinetic energy of water into mechanical energy and into electrical energy through a generator. The type of water turbine used in small-scale hydroelectric power plants, one of which is a verticalBwater turbine or crossflow turbine. Crossflow turbines have the advantageBof using water sources withBvarying flowBdirections, suchBas small rivers. This research method includes making a crossflow turbine prototype, based on the results of calculations in designing and testing a small-scale hydropower prototype that uses 37 bladesBwith a water height of 3 meters. The results of this research produced the highestBturbine power, namely 54,773 Watts, aBwater volume of 0.01 m³ with a water flow of 0.000003691 m³?s with a valve opening of 100°, while the lowestBturbine powerBwas 28,195 Watts, a water volume of 0.011 m³ with a water flow of 0, 000001190 m³?s withBa valve openingBof 75°, with the highest turbine efficiency value of 630.29% obtained when the water volume is 0.01 m³/s with aB100° valve,Bwhile theBlowest turbine efficiency is 1.006% at a water volume of 0.011m³/s s, and the maximum output obtained from testing the vertical water turbine prototype is at a water volume of 0.009 m³ with aBvalve opening of 100° whichNproduces aBturbineBrotation of 142.6 rpm, while at a water volume of 0.011 m³ with a valve opening of 75° which produces a turbineBrotation of 104.1 rpm,BwhileBtheBwater volumeBis 0.01 m³ withBa valveBopening of 100° whichIproduces a turbine rotation of 222.3 rpm, and while the water flow is 0.01 m³ with a valve opening of 75° whichIproduces a turbineIrotationIof 121.6 rpm.